Thermoelectric behavior of Al/PTFE reactive materials induced by temperature gradient. (April 2021) - Chen, Chuang; Gao, Renkui; Guo, Kai; He, Liping; Chang, Mengzhou; Han, Yafei; Tang, Enling
Abstract: In order to reveal the physical effect of Al/PTFE (mass percentage of 50%/50%) heat conduction and deflagration reaction induced by temperature gradient under the condition of flame heating, the loading and testing systems of cookoff experiment were conducted to measure the thermal response and electrical output characteristics of Al/PTFE before and after deflagration induced by temperature gradient. The thermal shock wave and thermoelectromotive force before deflagration, voltage signal induced by flame plasma expansion after deflagration were measured simultaneously. Meanwhile, the flash signal and the evolutionary process of flame region and temperature after deflagration were obtained. The results show that the thermal shock wave was generated by emergent temperature change in the stage of heat conduction, and the thermoelectromotive force was generated by the superposition of temperature gradients in different regions. The thermoelectromotive force can be equivalent to the series connection of electric source in each striped region. Under the temperature gradient of 6-10 K/mm, the maximum thermoelectromotive force can reach 0.8 V. Before deflagration, the local phase transition of molten or gaseous state induced by thermal decomposition destroyed the stable distribution of the temperature gradient of the sample, which leads to the decrease of the thermoelectric force. Based on the electric output signal of flame plasma, the reaction was divided into two stages including deflagration stage (lasting for 2–3 s) and stable combustion stage (lasting for about 10s). The average temperature of flame first increased and then decreased abruptly. The maximum temperature was 1585 K, and the propagation rate of flame was about 81.6 m/s in the initial stage of deflagration; however, the average temperature of the flame decreased slowly in the stable combustion stage, there was no obvious electrical output and the flash intensity decreased.